SOCIO-ECONOMIC DEVELOPMENT AND MODERN INTERNATIONAL RELATIONS OF POST-SOVIET COUNTRIES - Akhundova Chinara (2019)
The Commonwealth of Independent States is one of the unique international organizations, because unlike other international structures created at the international level by recognized, legitimate subjects of international law, its formation took place in parallel with the sovereignty of its members. The formation of the Commonwealth was the primary reaction of the former republics of the USSR to its collapse. The further development of this association fully reflected the complex processes of arranging the territory of the former Union. It is no accident that the abbreviation "CIS" in practice has become synonymous with the concept of "post-Soviet space minus the Baltic states." The actual direction of the activity of the leaders of the countries of the Commonwealth is solving the problems of implementing integration cooperation programs, the benefit of which is due to the fact that, firstly, you can use the previously created economic, based on the intra-industry division of labor, and cultural ties, and, secondly, regional associations, which in the modern world are a generally accepted way of the “normal” existence of states. This work is devoted to the expound of major trends, features and results of social and economic development of the post-Soviet countries and their cooperation during twenty years of independence. Based on the analysis of social arid economic dynamics of the new independent states since 1991, I attempt to answer the following questions: how the new economy of these countries was formed in cardinally changed conditions, and what role the Soviet heritage and the new realities – in particular, rapidly changing world and regional market conditions – played in this process. In the thesis interdependence between the level of social and economic development of the countries and specific forms of their integrational cooperation in different periods of the past twenty years is revealed. I tried to try to present a typology of the countries by factors and resources of development